Application Of The CAI Method Of Learning Signs-Traffic Signs For Early Childhood Based On Android - Satria Yudha Prayogi (Cattleya Darmaya Fortuna, 2019)
Traffic signs are part of road safety equipment that contains symbols that serve to convey messages to road users or traffic in an effort to bring order, make it comfortable and safe for road users and the activities of the people around them. Obeying traffic signs for safety and traffic order is very important to avoid accidents and violations of traffic rules. Learning and awareness of the importance of traffic signs needs to be instilled in the community from an early age. Learning is more interesting with the CAI method, which makes early childhood happy in learning the material presented. Early childhood is able to understand the signs presented in the android application.